RAISING SPIRITUALITY IN THE NEIGHBOURHOOD - Mamatqulova Munira Muxtorovna; Hudoyberdiyeva Latofat Abdumo’minovna; Ochilova Nigora Normurodovna (Research Parks Publishers, 2020)
This article discusses raising spirituality in the neighborhood and its role in the development of country. On this case, research has been pinpointed on different raising spirituality in the neighborhood. It will be indicated with outcomes and shortcomings of the different spiritual features